Inelastic Neutron Scattering Study of Phonon Dispersion Relation in Higher Manganese Silicides - Randy Belanger; James Patrick Clancy; Sheetal Jain; Zahra Yamani; Yu-Chih Tseng; Young-June Kim (Crystals, 2023)
We report inelastic neutron scattering (INS) measurements of the phonon dispersion relation in higher manganese silicides (HMSs). A large ingot of HMS is synthesized using a slow cooling method, which is found to have Mn<semantics>15</semantics>Si<semantics>26</semantics> as the primary phase. The sample is composed of highly oriented crystallites as confirmed by a neutron pole-figure study and thermal conductivity data. Our INS results are mostly consistent with earlier experimental and theoretical phonon studies in HMS, including the presence of a low-lying twisting mode. However, some discrepancies are also observed. Most notably, a 5 meV gap at the zone center and the softer dispersion relation of the low-lying twisting mode. We discuss the potential origins of these observations and their implications for the thermal properties of HMS.